Policies, political-economy, and Swidden in southeast asia - Jefferson Fox (2018)
For centuries swidden was an important farming practice found across the girth of Southeast Asia. Today, however, these systems are changing and sometimes disappearing at a pace never before experienced. In order to explain the demise or transitioning of swidden we need to understand the rapid and massive changes that have and are occurring in the political and economic environment in which these farmers operate. Swidden farming has always been characterized by change, but since the onset of modern independent nation states, governments and markets in Southeast Asia have transformed the terms of swiddeners' everyday lives to a degree that is significantly different from that ever experienced before. In this paper we identified six factors that have contributed to the demise or transformation of swidden systems, and support these arguments with examples from China (Xishuangbanna), Laos, Thailand, Malaysia, and Indonesia. These trends include classifying swiddeners as ethnic minorities within nation-states, dividing the landscape into forest and permanent agriculture, expansion of forest departments and the rise of conservation, resettlement, privatization and commoditization of land and land-based production, and expansion of market infrastructure and the promotion of industrial agriculture. In addition we note a growing trend toward a transition from rural to urban livelihoods and expanding urban-labor markets.